Munich & the Bavarian Alps - Galicka, Izabella; Michalska, Katarzyna; Pasieczny, Robert G.; Szatanska, Dorota (London Dorling Kindersley Limited, 2014)
Includes cutaways, floorplans and reconstructions of the must-see sites, and street-by-street maps of all the cities and towns of Munich & the Bavarian Alps. This title helps you discover everything region-by-region; from local festivals and markets to day trips around the countryside.
"Reprinted with revisions"--Title page verso.
Includes index.
Keywords: Munich (Germany) -- Guidebooks; Bavaria (Germany) -- Guidebooks; Alps, Bavarian (Germany) -- Guidebooks; Alps, Bavarian (Germany) -- Description and travel